2014
DOI: 10.1377/hlthaff.2013.1397
|View full text |Cite
|
Sign up to set email alerts
|

‘Pharmacy Deserts’ Are Prevalent In Chicago’s Predominantly Minority Communities, Raising Medication Access Concerns

Abstract: Attempts to explain and address disparities in the use of prescription medications have focused almost exclusively on their affordability. However, the segregation of residential neighborhoods by race or ethnicity also may influence access to the pharmacies that, in turn, provide access to prescription medications within a community. We examined whether trends in the availability of pharmacies varied across communities in Chicago with different racial or ethnic compositions. We also examined the geographic acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 19 publications
8
142
2
Order By: Relevance
“…This conclusion is consistent with Qato et al, which found that pharmacy deserts are more prevalent in predominantly minority neighborhoods. 21 This association is concerning because Black and Hispanic or Latino populations are disproportionately affected by Ct, which is the most common notifiable STI targeted by EPT. 22 Inadequate pharmacy access may impede treatment of infections, potentially maintaining high STI prevalence and increasing the likelihood of further transmission in these communities.…”
Section: Commentmentioning
confidence: 99%
“…This conclusion is consistent with Qato et al, which found that pharmacy deserts are more prevalent in predominantly minority neighborhoods. 21 This association is concerning because Black and Hispanic or Latino populations are disproportionately affected by Ct, which is the most common notifiable STI targeted by EPT. 22 Inadequate pharmacy access may impede treatment of infections, potentially maintaining high STI prevalence and increasing the likelihood of further transmission in these communities.…”
Section: Commentmentioning
confidence: 99%
“…A set of independent variables was chosen on the basis of regional socio-economic features, previous research (Casey et al, 2002;Perez and Decoupigny, 2009;Amstislavski et al, 2012;Norris et al, 2014;Qato et al, 2014) and data availability at the municipal level. This dataset included population (1000s of inhabitants)/population density (inhabitants per km 2 ), mean altitude (100 m units) above the mean sea level (msl), dummy variables of the status of rural according to the Eurostat classification (Istat, 2014), municipality (0=urban), coastal municipality (0=landlocked), proportion of >65-year-olds, <5-yearolds, immigrants, and a proxy of municipal income (mean declared personal income per taxpaper in 1000s of Euro).…”
Section: Study Variables and Data Sourcesmentioning
confidence: 99%
“…Limited geographical access not only reduces the availability of pharmaceuticals but also limits recommendations regarding their use (Norris et al, 2014). Qato et al (2014) and Amstislavski et al (2012) have even coined the terms pharmacy deserts and medication deserts, respectively, to describe neighbourhoods where geographic access to pharmacies and the availability of commonly used drugs are poor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study in Chicago found that there were fewer pharmacies in minority communities compared with white or integrated communities and that the disparity is worsening. 12 The researchers concluded that public policy changes should be considered, such as increased prescription reimbursement rates for community pharmacies located within pharmacy deserts and including pharmacies in community health centers. Disparities can also exist within communities that appear that have an adequate distribution of communities pharmacies.…”
Section: Accessing Health Servicesmentioning
confidence: 99%